Nigeria’s Corruption Score Card - STOBER, Emmanuel Olusegun (Management Dynamics in the Knowledge Economy, 2019)
Corruption in Nigeria is so lucrative that the threat of jail term is not enough to deter perpetrators, and the president’s body language is also worsening the situation. The National Bureau of Statistics has estimated 4.6 billion as the cost of corruption in Nigeria, confirming the country’s worsening Corruption Perceptions Index of the Transparency International. Nigeria’s 2018 CPI ranking became worst-off after scoring 27 out of 100 points, far below the world average of 43, and Sub-Sahara Africa average of 32.02. Given that Transparency International relies on the perception of institutions rather than measuring actual corruption experiences of the citizens, this study is set out to capture the experience of the latter. The study employs a quantitative research methodology based on a sociological questionnaire. The findings reveal robust evidence that corruption reacts to standard economic incentives, as it is tagged as an economic cost of getting the job done. Corruption, therefore, became institutionalized and thus a telling effect on the emerging political culture and behavior. The anticorruption strategy has also been that of media trial and seizure of accused persons’ assets. Hence the effects of anti-corruption policies are often weakening as businessmen, politicians and public officials often find alternate strategies for rent seeking.